An unusual complication during implantation of an internal cardioverter-defibrillator: A Case Report. Issue 2 (2017) - Monga, Shveta; Imam, Atique; Bulbulbia, Richard; Foley, Paul; Crea, William Mc; Chandrasekaran, Badrinathan
No abstract available